Usefulness of current candidate genetic markers to identify childhood cancer patients at risk for platinum-induced ototoxicity: Results of the European PanCareLIFE cohort study. (October 2020) - Langer, Thorsten; Clemens, Eva; Broer, Linda; Maier, Lara; Uitterlinden, André G.; de Vries, Andrica C.H.; van Grotel, Martine; Pluijm, Saskia F.M.; Binder, Harald; Mayer, Benjamin; von dem Knesebeck, Annika; Byrne, Julianne; et al.
Abstract: Background: Irreversible sensorineural hearing loss is a common side effect of platinum treatment with the potential to significantly impair the neurocognitive, social and educational development of childhood cancer survivors. Genetic association studies suggest a genetic predisposition for cisplatin-induced ototoxicity. Among other candidate genes, thiopurine methyltransferase ( TPMT ) is considered a critical gene for susceptibility to cisplatin-induced hearing loss in a pharmacogenetic guideline. The aim of this cross-sectional cohort study was to confirm the genetic associations in a large pan-European population and to evaluate the diagnostic accuracy of the genetic markers. Methods: Eligibility criteria required patients to be aged less than 19 years at the start of chemotherapy, which had to include cisplatin and/or carboplatin. Patients were assigned to three phenotype categories: no, minor and clinically relevant hearing loss. Fourteen variants in eleven candidate genes ( ABCC3, OTOS, TPMT, SLC22A2, NFE2L2, SLC16A5, LRP2, GSTP1, SOD2, WFS1  and ACYP2 ) were investigated. Multinomial logistic regression was performed to model the relationship between genetic predictors and platinum ototoxicity, adjusting for clinical risk factors. Additionally, measures of the diagnostic accuracy of the genetic markers were determined. Results: 900 patients were included in this study. In the multinomial logistic regression, significant unique contributions were found from SLC22A2 rs316019, the age at the start of platinum treatment, cranial radiation and the interaction term [platinum compound]∗[cumulative dose of cisplatin]. The predictive performance of the genetic markers was poor compared with the clinical risk factors. Conclusions: PanCareLIFE is the largest study of cisplatin-induced ototoxicity to date and confirmed a role for the polyspecific organic cation transporter SLC22A2 . However, the predictive value of the current genetic candidate markers for clinical use is negligible, which puts the value of clinical factors for risk assessment of cisplatin-induced ototoxicity back into the foreground. Highlights: A coding polymorphism in SLC22A2 was associated with platinum induced ototoxicity. Other genetic markers were not significantly associated with platinum ototoxicity. Results do not support preemptive genetic testing as recommended in a guideline. Identifying patients at high risk of platinum ototoxicity remains a challenge. Compared to genetic markers, clinical factors have a much higher predictive value.